PENGARUH AUDIT TENURE, FEE AUDIT, KOMITE AUDIT, DAN UKURAN PERUSAHAAN TERHADAP KUALITAS AUDIT : THE EFFECT OF AUDIT TENURE, AUDIT FEE, AUDIT COMMITTEE, AND COMPANY SIZE ON AUDIT QUALITY - Pamungkas, Setya Aji; Purnamasari, Dian Indri; Windyastuti , Windyastuti (Universitas Riau, 2022)
This study aims to examine the influence of audit tenure, audit fees, audit committee, and company size on audit quality. The population of this study is food and beverages listed on the Indonesian Stock Exchange with a new classification, namely Industrial Calcification (IDX-IC) for the period 2018-2020. Sampling was done by purposive sampling method, then the sample is 39 companies. This research was conducted by using logistic regression analysis. The results of this study indicate that audit tenure and audit fees have an impact on audit quality. The audit committee and company size do not affect audit quality.